High‐Barrier‐Height Ti3C2Tx/Si Microstructure Schottky Junction‐Based Self‐Powered Photodetectors for Photoplethysmographic Monitoring. Issue 12 (28th June 2022) - Song, Longmei; Xu, Enze; Yu, Yongqiang; Jie, Jianyong; Xia, Yu; Chen, Shirong; Jiang, Yang; Xu, Gaobin; Li, Dachuang; Jie, Jiansheng
Abstract: A high Schottky barrier height (ΦB ) is one of the essential prerequisites for achieving high‐performance self‐powered Schottky‐barrier diode (SBD)‐based photodetector. The ΦB value is predominantly determined by the metal function and interface quality of the metal/semiconductor contact. 2D MXenes with adjustable work functions and dangling bond‐free properties are promising building blocks for constructing self‐powered SBD with high ΦB . Herein, a novel Ti3 C2 T x MXene/Si hexagonal microhole array (SiHMA) van der Waals SBD is developed for the first time via a feasible solution process. Significantly, the device possesses a large ΦB up to ≈1.07 eV, which is among the highest for the Si‐based SBD. In consequence, the Ti3 C2 T x /SiHMA SBD yields a large responsivity up to 302 mA W −1 and detectivity as high as 5.4 × 10 13 Jones in a self‐powered model, surpassing the performance of most 2D material/Si photodiodes reported to date. Furthermore, it is demonstrated that featured and reliable fingertip photoplethysmogram (PPG) signals can be detected using the self‐powered SBD, enabling us to further accurately extract the heart rate (HR), and blood pressures (BP) using the PPG‐only method. This work paves the way for the construction of high‐performance MXenes‐based self‐powered SBDs for health monitoring. Abstract : Ti3 C2 T x /Si hexagonal microhole array Schottky‐barrier diode is constructed, which possesses a high Schottky barrier height of ≈1.07 eV, giving rise to excellent performance of the photodetector in a self‐powered model. Featured and reliable fingertip photoplethysmogram (PPG) signals can be detected by using the photodetector, enabling the accurate extraction of the heart rate and blood pressures based on the PPG‐only method.